Value of Glycogen Synthase 2 in intrahepatic cholangiocarcinoma prognosis assessment and its influence on the activity of cancer cells - Sigen A (Taylor & Francis Group, 2021)
Intrahepatic cholangiocarcinoma is the second most common primary liver tumor with increasing incidence worldwide. Metabolic reprogramming caused by metabolic related gene disorders is a prominent hallmark of tumors, among which Glycogen Synthase 2 (GYS2) is the key gene responsible for regulating cellular energy metabolism, and its expression disorders are closely related to various tumors and glycometabolic diseases. However, we still know nothing about its role in intrahepatic cholangiocarcinoma. The purpose of this study was to uncover the functional role of GYS2 in the progression ICC and explore the underlying mechanism. Firstly, we performed an integrated pan-cancer analysis of GYS2 in the Gene Expression Profiling Interactive Analysis database and further detected the expression of GYS2 in paired intrahepatic cholangiocarcinoma and adjacent non-tumor tissues by qPCR, then we analyzed the relationship between the expression level and clinicopathologic factors as well as the effect on the survival of patients. Finally, we identified the effect on the biological behavior of cholangiocarcinoma cells by cellular and molecular experiments. The expression of GYS2 was significantly downregulated in intrahepatic cholangiocarcinoma. The low expression of GYS2 was not only associated with the degree of pathological differentiation, tumor size, microvascular invasion and lymph node metastasis, but also an independent risk factor for unfavorable prognosis. Functional studies have shown that GYS2 overexpression can significantly impair the proliferation, replication, cloning, migration and invasion of cholangiocarcinoma cells, while the silencing GYS2 dramatically promotes the development of the aforementioned phenotypes, the underlying mechanism may be that GYS2 activates the P53 pathway. In conclusions, low GYS2 expression in intrahepatic cholangiocarcinoma predicted unfavorable patient outcomes; GYS2 overexpression can significantly impair the proliferation, migration and invasion of cholangiocarcinoma cells via activating the P53 pathway and GYS2 was expected to become a potential therapeutic target for such patients.